Evaluating the Use of Telemedicine in Endocrinology Clinic - Nemati, Maryam (J Endocr Soc, 2021)
The COVID-19 pandemic changed patient-physician interaction. As the need to reduce COVID-19 transmission, many clinic providers have converted their in-person visits to video or phone visits. Our endocrinology clinic initiated tele visits early on when the pandemic had just started. Telemedicine may help with patient’s compliance by decreasing various burdens. Some studies show that patients and providers hope telemedicine will continue after the crisis. In this study we evaluated benefits and challenges of telemedicine in our endocrinology clinic. Patients who had a telemedicine endocrinology visit after informed consent were surveyed on 10 questions regarding benefits and limitations of the tele visits compared to the clinic visit. Patient also responded if they want to continue with telehealth after COVID-19 pandemic. Providers also were surveyed about the benefits and limitations of telemedicine and responded if they want to continue with telemedicine after pandemic. We also analyzed no-show rate from January 2020 through May 2020 for 6 weeks before and after the implementation of telemedicine. Among 109 patients who were interviewed 65% declared that they would like to continue with telemedicine after pandemic. Total of 42% of patients prefer video visit and 37% prefer phone calls. Among Interviewers 45% report benefit of spending less time, however 54% stat the time of meeting, itself was about the same. 54% believe they spent less money with telemedicine. 37% of interviewers report no limitation for telehealth while 25% report connection difficulty. 63% of patients state they do not have any difficulty traveling to the hospital. 90% of the patients declare all their question and concerns were responded and 77% stated the quality of care with telemedicine is almost the same via clinic visit. Among providers 75% want to continue telehealth after COVID-19 pandemic. 50% of providers mention patient satisfaction and 25% notice time saving as benefits. 46% of the providers mention lack of physical exam and 40% mention technology connection as the limitation for video visit. 60% of providers believe lack of exam is the limitation of phone visit. 87% of the providers believe the quality of care via phone is not like in clinic visit while 75% of the providers believe the quality of care is similar in video visit compare to in clinic visits. No show rate decreased from 30% to 27% after the implementation of telemedicine in 6 weeks prior and after pandemic. Endocrinology clinic has significant number of patients who need long term close follow up for medication adjustments, symptom checks and counseling. Given patients and providers satisfaction rate, telemedicine can be incorporated as part of regular clinic visits after the Covid crisis ends. Telehealth can be more efficient for both patients and providers but there are challenges which needs to be addressed.